Pengaruh Lingkungan Pemasaran Global terhadap Perekonomian di Indonesia - Suhairi Suhairi; Nurul Hayati Panjaitan; Laila Annisyah Lubis; Djauky Ridho Amwa (Departement of Mathematics Education, 2023)
The success of global companies in the Indonesian market is due to their ability to package global marketing strategies that are adapted to the Indonesian market, both politically, economically, socio-culturally, geographically and economically. The purpose of this research is to find out how the influence of the existence of a global marketing environment has on the economy in Indonesia. This study uses a descriptive analysis method, which is a method that describes the results of problem analysis in order to answer research problems. In this case, analyzing global marketing issues for Indonesian companies to compete in the global market. The results obtained from this study are global marketing strategies for Indonesian national companies. Obtaining data is done through library research methods (library research). Global marketing can bring positive and negative influences, it all depends on how domestic marketing deals with it. With all its policies, the government's role is inevitably very important in advancing the Indonesian economy in facing the global market.